Massless scalar fields in non-abelian kaluza-klein theory - M., Arik; V., Gabay (World Scientific Pub Co Pte Lt, 1994)
We investigate the presence of massless scalar fields in a Kaluza—Klein theory based on a dimensionally continued Euler-form action. We show that massless scalar fields exist provided that the internal space is a direct product of two irreducible manifolds. The condition of a vanishing effective four-dimensional cosmological constant and the presence of a graviton, gauge fields and massless scalar fields can be satisfied if both irreducible manifolds have odd dimensions and the sum of these dimensions is equal to the dimension of the Euler form.
Keywords: Kaluza-Klein and other higher-dimensional theories